Strategi Penggunaan Instagram Reels dalam Meningkatkan Engagement Konten Dakwah di Kalangan Mahasiswa UINSU - Nawaf, Azmi; Naad, Darul; Hambali, Muhammad; Sikumbang, Ahmad Tamrin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The advancement of digital technology, particularly social media, has transformed the way dakwah is delivered, especially among the younger generation. This study focuses on the use of Instagram Reels as a platform to increase engagement with dakwah content among UINSU students. The problem addressed in this research is how appropriate strategies can be employed to attract audience attention and enhance involvement in dakwah content. Through a qualitative approach, data were collected from literature reviews and observations of UINSU students' use of Instagram Reels. The findings indicate that dakwah content presented in short video formats (15-30 seconds) with clear and creative messages effectively captures students' attention. Factors such as message relevance, interactivity, and creativity in content presentation play crucial roles in boosting engagement. Content addressing current issues relevant to students' daily lives, along with encouraging active audience participation, achieved higher interaction levels. Additionally, the timing of posts also significantly influences the success of attracting the audience. The conclusion of this study emphasizes that Instagram Reels holds substantial potential as an effective medium for dakwah to enhance engagement. Therefore, dakwah content creators are encouraged to implement strategies that focus on authenticity, relevance, and creativity to convey religious messages effectively in the digital era. This research is expected to provide insights for preachers and practitioners of dakwah in formulating more innovative and adaptive communication approaches tailored to the characteristics of the younger generation.